2000
DOI: 10.1038/sj.sc.3101065
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the in vitro characteristics of osteoblasts from paralytic and non-paralytic children

Abstract: Study design: Cerebral palsy is known to provoke a high loss of bone in children and adults. The potential interest of human osteoblastic cell culture for assessing the osteoblastic function in metabolic bone disorders has been demonstrated by many previous studies. Few studies have attempted to evaluate the capacities of osteoblasts isolated from immobilized or normal bones by in vitro culture methods. Moreover, a few teams did make the distinction between young spastic and¯accid patients. Objectives: We atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Leptin administration leads to a significant increase in femoral length, total body area, as well as bone mineral content and bone density [Liu et al, 1997;Matkovic et al, 1997;Iwaniec et al, 1998;. Other reports, however, assert that leptin inhibits bone formation through a central nervous regulatory loop [Anselme et al, 2000;Ducy et al, 2000;Fleet, 2000], claiming that there is no leptin signaling in osteoblastic cells. Our findings are substantiated by the very recent report by Bassilana et al (2000), demonstrating that human mesenchymal stem cells, when differentiated, express leptin and leptin receptor isoforms, as well as leptin-induced phosphorylation of STAT3.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Leptin administration leads to a significant increase in femoral length, total body area, as well as bone mineral content and bone density [Liu et al, 1997;Matkovic et al, 1997;Iwaniec et al, 1998;. Other reports, however, assert that leptin inhibits bone formation through a central nervous regulatory loop [Anselme et al, 2000;Ducy et al, 2000;Fleet, 2000], claiming that there is no leptin signaling in osteoblastic cells. Our findings are substantiated by the very recent report by Bassilana et al (2000), demonstrating that human mesenchymal stem cells, when differentiated, express leptin and leptin receptor isoforms, as well as leptin-induced phosphorylation of STAT3.…”
Section: Discussionmentioning
confidence: 94%
“…Most importantly, it was shown that leptin preferentially induced differentiation of stromal cells into osteoblasts [Thomas et al, 1999;Marie et al, 2000] and chondrocytes, but also adipocytes [Marie et al, 2000], depending on incubation conditions. However, some researchers [Anselme et al, 2000;Ducy et al, 2000;Fleet, 2000] failed to identify leptin receptors in osteoblasts, and advocate a strict neuroendocrine and indirect regulation of bone metabolism and function by leptin. The contradicting in vivo results provide a need for more investigation.…”
mentioning
confidence: 96%
“…LeggPerthes-Calve disease is an idiopathic avascular necrosis of the femoral head, which does not affect the iliac crest. Bone marrow was extracted as previously published in details (Anselme et al 2000). Briefly, a small part of the body iliac crest was removed at the end of the surgery in order to close without creating tension of the iliac crest.…”
Section: Cell Culturementioning
confidence: 99%
“…Peripheral influences of leptin on bone remodeling have been reported in adults, but fewer studies have concerned children [14, 15]. The effects of leptin on growth plate chondrocytes have not been described.…”
Section: Introductionmentioning
confidence: 99%